Rehabilitating a Mythology: The Ukrainian SSR's Foundational Myth After Stalin. Issue 3 (18th June 2019) - Dobczansky, Markian
Abstract: This article looks at the rehabilitation of the early history of the Communist Party of Ukraine and the Ukrainian SSR during the Thaw. It argues that the post-Stalin political moment offered the Ukrainian Party and academic establishments the opportunity to revalorize their republic's founding narrative. In order to popularize this narrative, they produced publications on the revolution in Ukraine and early party history, rehabilitated Ukrainian Communists from the 1920s who had fallen victim to repressions, and constructed a set of monuments that embodied the new historical paradigm. These efforts aimed to de-Stalinize the country's history as well as promote a Soviet Ukrainian patriotism that would make Ukrainians feel more integrated into the Soviet whole. Based on archival research, newspapers, and memoirs, the article suggests that rehabilitating this narrative was a strategy for the legitimization of the party within Ukraine.